KONSTRUKSI MAKNA DAN KOORDINASI KOMUNIKASI TIM KREATIF DALAM PRODUKSI PROGRAM KULINER JAN ENAK TENAN MNC CHANNELS - Fitriyanti, Syahla; Suriaatmaja Suwanda, Bayu; Kuntoro, Diadji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The increasingly competitive media industry requires television programs to maintain quality through effective communication and coordination among production team members. Jan Enak Tenan, a culinary program broadcast by MNC Channels, presents information about culinary destinations from various regions in Indonesia in an informative and entertaining format. This study aims to examine the construction of meaning and communication coordination among the creative team in the production process of Jan Enak Tenan. This research employed a qualitative approach with a descriptive method. Data were collected through in-depth interviews, observations, and documentation involving the producer, creative team, and Production Assistant as informants. Data analysis used the Miles and Huberman model, including data reduction, data presentation, and conclusion drawing. The findings show that the construction of meaning within the production team was formed through discussions, briefings, and exchanges of ideas that created a shared understanding regarding the objectives and concepts of the program. Communication coordination was carried out intensively through production meetings, briefings, and communication media such as WhatsApp groups. The study also found communication barriers, including schedule changes, location changes, and differences of opinion in the creative process, which were resolved through rapid communication and continuous coordination. These findings are consistent with the Coordinated Management of Meaning (CMM) theory proposed by Pearce and Cronen, which explains that meaning and collective actions adcommunication plays an important role in supporting the success of the production process of Jan Enak Tenan on MNC Channels.